Seventh-Day Adventism in Africa - Masfa, Gabriel, author.
1 online resource
Keywords: "This book examines the complex history of Adventism in Africa, situating it within the context of African traditions and culture. From a small movement with origins in the United States, the Seventh-day Adventist Church has grown worldwide. It is one of several Christian denominations present in Africa and yet the history of Seventh-day Adventism in the global South has been largely unexplored by scholars. The book highlights the discrepancies between western traditions exhibited in the missionary enterprise and African religious systems. It also explores the intricate relation between colonialism and African Adventism in line with established studies in African Christianity. It will be of interest to scholars of religion and theology, particularly church history and mission studies, as well as African studies"--